If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13x + -1(x + 7) = 29 Reorder the terms: 13x + -1(7 + x) = 29 13x + (7 * -1 + x * -1) = 29 13x + (-7 + -1x) = 29 Reorder the terms: -7 + 13x + -1x = 29 Combine like terms: 13x + -1x = 12x -7 + 12x = 29 Solving -7 + 12x = 29 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 12x = 29 + 7 Combine like terms: -7 + 7 = 0 0 + 12x = 29 + 7 12x = 29 + 7 Combine like terms: 29 + 7 = 36 12x = 36 Divide each side by '12'. x = 3 Simplifying x = 3
| 25=9+9(8xf) | | 42j+18-19j=28 | | 3=-6+x | | 7(2x-4)=28 | | 8=14+x | | 25-9= | | 10(5x-3)=20 | | 6+x=23 | | 5x-8=32 | | X-20=-7 | | 17+3x-11=0 | | 3(4x-7)=105 | | -2(4a+3)-5(2-a)=3(2a+3)-7 | | 7x=-6x+9 | | 3m+4.5m=15 | | 4x-8-x=22 | | 3.5=17s-5s | | -7(4x-7)=105 | | 0.11p+1.5=2.49 | | 1.12+1.125y=8.62 | | -x-9+7x=21 | | 0.25m+0.1m=9.8 | | -(z+5)=-14 | | 5x+6= | | 5(4+p)=3(3p-1)-9 | | m(2)+4(15.5)=m+4(3) | | 5x-7=0 | | 0.5(x-12)=4 | | 5n+10=5 | | 29=a+5 | | 8(3x+1)=-80 | | -2=-(2-8) |